Pengaruh Work Life Balance dan Stres Kerja Terhadap Kinerja Guru MTs Negeri di Jakarta Barat - Nabilah Khonsa; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
The problem of declining teacher performance is still a problem in today's education world. The imbalance between work-life balance and work stress makes teacher performance decline. Work-life balance and work stress are components that greatly influence teacher performance. The purpose of this study was to determine the effect of work-life balance on teacher performance, to determine the effect of work stress on teacher performance, and to determine the relationship between work-life balance and work stress in influencing the performance of MTs Negeri teachers in West Jakarta. The research method used in this study is the Systematic Literature Review (SLR), to obtain and review scientific literature on the effect of work-life balance and work stress on teacher performance. The results of the study showed that work-life balance has a significant effect on teacher performance, where teachers who are able to balance their personal lives and work show better performance. In addition, work stress has a positive or negative effect on teacher performance, depending on the intensity of the stress experienced. Work-life balance and work stress are interrelated in influencing teacher performance. When work-life balance is achieved, work stress can be managed better, and teacher performance will increase. The results of this study are very important in order to determine the effect of work-life balance and work stress on teacher performance.